2019
DOI: 10.1177/0959683619892661
|View full text |Cite
|
Sign up to set email alerts
|

14 kyr of atmospheric mineral dust deposition in north-eastern China: A record of palaeoclimatic and palaeoenvironmental changes in the Chinese dust source regions

Abstract: A multi-proxy record of Holocene and late-Pleistocene aeolian mineral dust is reconstructed using a combination of geochemical (trace elements), mineralogical and grain-size analyses on cores from the Hani peatland in north-eastern (NE) China. The dust record displays a sharp increase in dust deposition during the late Holocene in comparison to the rest of the Holocene. This trend is in line with climatic records from the Chinese dust source regions and their downwind areas, which generally show an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 134 publications
0
11
0
Order By: Relevance
“…The PCA of the XRF data grouped Zr, Ti, Si and Al onto Cp2 XRF (Table 4). These elements are commonly hosted in zircon, rutile, quartz, feldspars and clay and are conservative lithophile elements often used as indicators of mineral input to bogs (e.g., Longman et al, 2017;Pratte et al, 2019;Shotyk et al, 2001;Weiss et al, 2002). While Si can be hosted in biogenic phases like diatoms and phytoliths, the association with elements hosted in conservative minerals suggests an inorganic origin for Si.…”
Section: Characterising the Inorganic Fraction Of The Smds Peat Sequencementioning
confidence: 99%
“…The PCA of the XRF data grouped Zr, Ti, Si and Al onto Cp2 XRF (Table 4). These elements are commonly hosted in zircon, rutile, quartz, feldspars and clay and are conservative lithophile elements often used as indicators of mineral input to bogs (e.g., Longman et al, 2017;Pratte et al, 2019;Shotyk et al, 2001;Weiss et al, 2002). While Si can be hosted in biogenic phases like diatoms and phytoliths, the association with elements hosted in conservative minerals suggests an inorganic origin for Si.…”
Section: Characterising the Inorganic Fraction Of The Smds Peat Sequencementioning
confidence: 99%
“…Freezing and thawing of the seasonally frozen ground may contribute to the slight rise of Ca at the 95-113 cm depth, corresponding to a period from 800 BCE to 1 AD. Nevertheless, the increase in value is much less than the 3-to 16-fold increase observed in basal minerogenic peat profiles (Pratte et al, 2019;Shotyk et al, 2001;Steinmann & Shotyk, 1997). Taken together, these suggest that mineral dissolution and element remobilization in Hulugou peat is low and hence it can be used as a geochemical dust archive.…”
Section: Dust Activities Of the Qilian Mountains During The Last 2800...mentioning
confidence: 82%
“…
Nevertheless, past dust activities are difficult to be quantified beyond instrumental time scale, whereas inferring past dust emissions and transport pathways is critical to understanding the regime of present and future dust activities. While there are several research papers on mineral dust particles emitted from dust sources that have archived climatic and environmental changes in terrestrial environments on an orbital scale (Ferrat et al, 2012;Pratte et al, 2019;Qiang et al, 2014), few studies of dust are based on the centennial-millennium scale. Among them, several studies have investigated the strong relationship between intensive dust storms and cold air cyclonic activities, such as those conducted by F. Chen et al (2013), Han et al (2019), and Wyrwoll et al (2016.
…”
mentioning
confidence: 99%
“…Some previous work also highlighted a range of other drivers behind peat accumulation rates, with mineral dust input listed as the primary driver of peat growth in a Swedish peatland (Kylander et al, 2018) and fluctuations in the supply of dust from the Loess Plateau in China found to be important in controlling local peat development (Pratte et al, 2020). We use the two existing peat records of Holocene dust deposition in the Romanian Carpathians to investigate this connec-tion (Longman et al, 2017b;Panait et al, 2019) in our study region (Fig.…”
Section: Comparison With Other Potential Driving Forcesmentioning
confidence: 99%